Desenvolvimento de um equipamento para avaliar propriedades elásticas de cerâmicas refratárias a altas temperaturas pelo método de ressonância de barras. - Paiva, Antônio Ernandes Macêdo (2002)
The knowledge of the elastic properties has been of fundamental importance for the understanding of the limitation of the useful life of structural refractory ceramics. Those properties characterize the elastic rigidity of the materials and represent a requirement for the specific classification of the materials and their mechanical characteristics. The determination of properties, such as, Young s modulus (E), shear modulus (G) and Poisson s ratio (µ) are important for the determination of several important mechanical properties. In this work the dynamic method of bar resonance was used to obtain those three elastics properties. It consists in the stimulation of a sample with variable frequency, in order to obtain the fundamental frequency and their harmonics of natural vibration of the body. Considering the density and the geometry of the sample the elastic properties of the material are obtained. Therefore, the objective of this work was to develop an automatic equipment to measure E, G and µ as a function of the temperature using the technique of bar resonance and a software that controls the system. As exemplification of the use of that software and of that equipment, a study of the influence of the aggregate s size (DL = 2800, 4750 and 8000 µm) and of the Andreasen s coefficient of particle size distribution (q = 0,21; 0,26 and 0,31) on the thermal shock damage in alumina refractory castables was accomplished. Besides, other study about the influence of the porosity on the elastic properties of cellular ceramics processed by gelcasting was also carried out. The dependence of E and G on the porosity according to models found in the literature was confirmed. The dependence of the elastic moduli on the temperature of for those foams was also evaluated.